Early summer iron limitation of phytoplankton photosynthesis in the Scotia Sea as inferred from fast repetition rate fluorometry. Issue 8 (2nd August 2013) - Park, Jisoo; Park, Taewook; Yang, Eun Jin; Kim, Dongseon; Gorbunov, Maxim Y.; Kim, Hyun‐Cheol; Kang, Sung Ho; Shin, Hyoung Chul; Lee, SangHoon; Yoo, Sinjae
Abstract : [1] We describe variability in the phytoplankton physiological status in the west Scotia Sea of the Southern Ocean in the early austral summer prior to and at the beginning of a phytoplankton bloom. This area is characterized by high concentrations of major nutrients (such as nitrate, phosphate, and silicate), but exhibit chronically low concentrations of dissolved iron and deep vertical mixing. Using a fast repetition rate fluorometry, we measured photosynthetic characteristics of phytoplankton in the euphotic zone. These measurements provide an express diagnostic of the effects of environmental factors, including iron limitation, on photosynthetic processes. The quantum yields of photochemistry in Photosystem II (Fv /Fm ) in subsurface phytoplankton were, on average, 40% lower than the maximum values for nutrient‐replete communities. Higher values of Fv /Fm were observed in the frontal mixing zone that may have been caused by the induction of iron into the euphotic layer. Our results suggest physiological signatures of iron limitation of photosynthesis in the western Scotia Sea in the early austral summer. The data imply that, together with light conditions and grazing pressure, iron availability may be important for phytoplankton growth in the Scotia Sea even in the early summer. Key Points: Characterized physiological status of phytoplankton in the western Scotia Sea. Revealed physiological signatures of iron limitation in early summer Discuss the importance of iron availability and physical forcing